EFEKTIFITAS KUNYIT ASAM UNTUK MENURUNKAN SKALA NYERI HAID (DISMENOREA) PADA REMAJA PUTRI TAHUN 2022 - Khoiriah, Restu (Journal of Midwifery Tiara Bunda, 2022)
Background: Dysmenorrhoea is abdominal pain in the lower part that occurs during menstruation sometimes extends to the waist, lower back and thighs. The cause of the occurrence of Dysmenorrhoea is the presence of an excessive amount of prostaglandins of F2α in the menstrual blood, thereby stimulating uterine hyperactivity and the occurrence of spasms of the uterine muscles. Objective: To find out the Relationship and Differences to the menstrual pain scale in class X students. Method: This type of research is pre exprerimenntal designs with a design of one group pre-test and post-test design. The population in this study was all class X students who were menstruating and experiencing menstrual pain. The sempel-taking technique is purposive sampling in accordance with the inclusion and exclusion criteria. Data processing using editing, coding, entery data, scoring, tabulating, with statistical test data analysis paired sample test. Result: Research on measuring the pre and post pain scale obtained results that from 35 respondents obtained a correlation of 0.539 with a significant value or p value of 0.001 so that it can be concluded that there is a relationship between pre and post test to a decrease in menstrual pain. The results of the pre and post effectiveness test of turmeric acid administration showed that the value of Asymp. Sig. is = 0.000 so the sig value < the value of α = 0.05 which means Ha is accepted. It can be concluded that there are differences before and after the administration of turmeric acid drinks against the decrease in the scale of menstrual pain in female students at SMAN 1 Kopo. Conclusion: There is a relationship and effectiveness of giving turmeric acid pre and post test.